EFFECTIVENESS OF LOCAL WISDOM-BASED TEACHING MATERIALS (FLOATING MARKET) ON GRADE IV SOCIAL STUDIES LEARNING OUTCOMES - Basuki, Lukita Ayu; Huriyah, Huriyah (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2025)
Abstract: The importance of teaching materials that are in accordance with the student environment while acquiring knowledge. It is expected providing teachers with the ability to apply local wisdom-based teaching materials that are around students. With This investigation is intended to explore the differences in teaching and learning sessions conducted earlier and later the application of learning content derived from local cultural values floating market to support students’ achievement in social studies outcomes. The study follows a fieldwork approach with a research design based on the one-group pre-test–post-test model. This research involved a population of students from grade IV SDN Kuin Selatan 1 Banjatmasin which amounted to 43 people. The learning results obtained in this study one can conclude that the substance of educational resources reflecting local traditions of the floating market is effectively used in social studies learning. This is known from the findings of the observation of the educational process activities in which a lot of students are active while the teaching and learning is taking place and outcomes of learning utilizing educational content based on local cultural values floating market category "Good".Keywords: Learning Results, Local Wisdom, Teaching Materials. Abstrak: Pentingnya sumber belajar yang berhubungan dengan keadaan lingkungan siswa dalam proses pembelajaran. Diharapkan guru mampu menerapkan bahan ajar berbasis kearifan lokal yang ada di sekitar siswa. Dengan penelitian ini bertujuan untuk mengetahui perbedaan kegiatan belajar Pengajaran dilakukan pada tahap pra dan pasca penerapan bahan ajar yang berbasis kearifan lokal pasar terapung, dengan tujuan meningkatkan pencapaian belajar siswa dalam mata pelajaran IPS. Penelitian ini bersifat lapangan dan menggunakan desain eksperimen one group pre-test post-test. Sebanyak 43 siswa kelas IV di SDN Kuin Selatan 1 Banjarmasin menjadi populasi dalam penelitian ini. Kesimpulan dari penelitian ini menyatakan bahwa penerapan bahan ajar yang mengangkat kearifan lokal pasar terapung mampu mendukung efektivitas pembelajaran IPS. Berdasarkan observasi terhadap proses pembelajaran, dapat dilihat bahwa banyak siswa yang menunjukkan keterlibatan aktif, dan Pencapaian hasil belajar siswa menggunakan bahan ajar yang berfokus pada kearifan lokal pasar terapung termasuk dalam kategori “Baik”. Kata Kunci: Bahan Ajar, Hasil Belajar, Kearifan Lokal.